Assessment of the potential of a laser-based device as a Rhipicephalus microplus motility inhibitor - Dos Santos, Leonardo Aparecido Lima [UNESP]; Vazquez, Velizie Caldarelli [UNESP]; Gainza, Yousmel Alemán [UNESP]; Chagas, Ana Carolina De Souza; Torres, Renato Cristiano; Felippelli, Gustavo [UNESP]; Minho, Alessandro Pelegrine (Colégio Brasileiro de Parasitologia Veterinária, 2025)
Rhipicephalus microplus is an ectoparasite responsible for causing economic losses in livestock farming totalling approximately $3.24 billion dollars per year. The main control method involves the use of chemical acaricides. However, the incorrect and intensive use of these chemicals has led to an increasing number of reports of resistance to acaricides. Therefore, the objective of this study was to develop and evaluate a laser prototype with a voltage of 5 V and power of 1000 mW to reduce the development of R. microplus. The methodology evaluated did not result in a high mortality rate; therefore, it was necessary to carry out a larval migration test. To carry out the test, 3 treatments were evaluated in triplicate (negative controls H20, 60% ethanol and positive control), with 20 larvae were evaluated for each replicate of the treatments, which resulted in an increase in the percentage of migration from 2.5% and 3.2% to above 94.9% and 93.5% in the negative controls, while in the positive control group there was no showed a significant change in migration, reaching close to 100%. This study demonstrated that physical control caused damage to ectoparasite locomotor structures and could affect the parasite's life cycle.

Rhipicephalus microplus é um ectoparasita responsável por causar perdas econômicas na pecuária, totalizando aproximadamente US$ 3,24 bilhões de dólares por ano. O principal método de controle envolve o uso de acaricidas químicos. Contudo, o uso incorreto e intensivo desses produtos químicos tem levado a um número crescente de relatos de resistência a acaricidas. Portanto, o objetivo deste estudo foi desenvolver e avaliar um protótipo laser com tensão de 5 V e potência de 1000 mW para reduzir o desenvolvimento do R. microplus. A metodologia avaliada não resultou em elevada taxa de mortalidade, portanto, foi necessária a realização do teste de migração larval. Para a realização do teste foram avaliados 3 tratamentos em triplicata (controles negativos H20, etanol 60% e controle positivo), sendo avaliadas 20 larvas para cada réplica dos tratamentos, que resultou no aumento da porcentagem de migração de 2,5% e 3,2% para acima de 94,9% e 93,5% nos controles negativos, enquanto o grupo controle positivo não apresentou alteração significativa na migração, ficando próximo de 100%. Este estudo demonstrou que o controle físico causou danos às estruturas locomotoras dos ectoparasitas, podendo afetar o ciclo de vida parasitário.
Avaliação da capacidade de um dispositivo a laser como inibidor da motilidade de Rhipicephalus microplus
Keywords: Tick; physical control; ectoparasite; resistance; Carrapato; controle físico; ectoparasita; resistência